Harnessing The Power of Imagination: Unraveling The Impact of Mental Exercise on Football Students' Performance In University - Ishak, Muhammad; Raswin, Raswin (Universitas PGRI Palembang, 2024)
This investigation delves into the symbiotic relation between physical and mental fitness, introducing imaginary exercise as a unique avenue for skill refinement in university-level football students. The study, situated at the intersection of sports, academia, and neuroscience, employs a comprehensive methodology encompassing participant selection, structured imaginary exercise protocols, neurocognitive measurements, and diverse performance metrics. Statistical results highlight significant improvements post-intervention, with a notable increase in accuracy from 75% to 85% (p < 0.001), indicating enhanced precision in executing football-related skills. The reduction in reaction time from 1.5 to 1.2 seconds is also statistically significant (p < 0.01), reflecting improved on-field responsiveness. Decision-making proficiency exhibits a significant improvement from 60% to 75% (p < 0.05), emphasizing the positive impact of mental exercises on strategic choices during simulated game scenarios. Situational awareness significantly increases from a pre-intervention score of 70 to a post-intervention score of 85 (p < 0.001), underlining the role of imagination in navigating complex on-field situations. Neurocognitive correlates unveil increased activation in relevant brain regions, establishing a neurobiological foundation for observed behavioral enhancements. The correlation between increased activation and improved accuracy (r = 0.75, p < 0.001) reinforces the interplay between neural processes and behavioral outcomes. Subjective insights from surveys and interviews align with quantitative findings, with 80% reporting increased confidence and 70% reporting improved focus and control. The innovative integration of virtual reality, deemed beneficial by 90% of participants, highlights its potential in enhancing mental conditioning for football students. This study provides robust statistical evidence supporting the transformative power of imagination in athlete development, emphasizing the integral role of mental conditioning in unlocking untapped potential on the football field.